Variation in supplemental lighting quality influences key aroma volatiles in hydroponically grown ‘Italian Large Leaf’ basil - Hammock, Hunter A.; Sams, Carl E. (Frontiers in Plant Science, 2023)
The spectral quality of supplemental greenhouse lighting can directly influence aroma volatiles and secondary metabolic resource allocation (i.e., specific compounds and classes of compounds). Research is needed to determine species-specific secondary metabolic responses to supplemental lighting (SL) sources with an emphasis on variations in spectral quality. The primary objective of this experiment was to determine the impact of supplemental narrowband blue (B) and red (R) LED lighting ratios and discrete wavelengths on flavor volatiles in hydroponic basil (Ocimum basilicum var. Italian Large Leaf). A natural light (NL) control and different broadband lighting sources were also evaluated to establish the impact of adding discrete and broadband supplements to the ambient solar spectrum. Each SL treatment provided 8.64 mol.m-2.d-1 (100 µmol.m-2.s-1, 24 h.d-1) photon flux. The daily light integral (DLI) of the NL control averaged 11.75 mol.m-2.d-1 during the growth period (ranging from 4 to 20 mol.m-2.d-1). Basil plants were harvested 45 d after seeding. Using GC-MS, we explored, identified, and quantified several important volatile organic compounds (VOCs) with known influence on sensory perception and/or plant physiological processes of sweet basil. We found that the spectral quality from SL sources, in addition to changes in the spectra and DLI of ambient sunlight across growing seasons, directly influence basil aroma volatile concentrations. Further, we found that specific ratios of narrowband B/R wavelengths, combinations of discrete narrowband wavelengths, and broadband wavelengths directly and differentially influence the overall aroma profile as well as specific compounds. Based on the results of this study, we recommend supplemental 450 and 660 nm (± 20 nm) wavelengths at a ratio of approximately 10B/90R at 100-200 µmol.m-2.s-1, 12-24 h.d-1 for sweet basil grown under standard greenhouse conditions, with direct consideration of the natural solar spectrum and DLI provided for any given location and growing season. This experiment demonstrates the ability to use discrete narrowband wavelengths to augment the natural solar spectrum to provide an optimal light environment across variable growing seasons. These results show how the spectral quality of SL can be used to optimize sensory compounds of sweet basil and provide a baseline to explore other high-value specialty crops.